0063 Incidence of knee pain and its work-related risk factors in a large working population. (23rd June 2014) - Herquelot, Eléonore; Leclerc, Annette; Roquelaure, Yves; Bodin, Julie; Ha, Catherine; Cyr, Diane; Goldberg, Marcel; Zins, Marie; Descatha, Alexis
Abstract : Objectives: This study aims to estimate the incidence of knee pain and its risk factors in a general French working population, representative of the work force. Method: Of 3710 workers of a French region included in a study in 2002–2005 with a self-administered questionnaire, 2332 completed a follow-up questionnaire in 2007–2011. The questionnaires included musculoskeletal symptoms, individual and occupational exposures, and physical limitations (at follow-up only). Incident knee pain in 2007–2011 (i.e. subjects not suffering of knee pain at baseline and suffering of knee pain at follow-up) was dichotomized into sub-chronic knee pain (1–29 days) and chronic knee pain (>30 days). Associations between the incident knee pains and individual and work-related risk factors at baseline were studied separately by gender, using multinomial logistic regressions. Results: Of the 1616 respondents without knee pain at baseline, 122 (7.5%) reported chronic knee pain and 243 (15.0%) reported sub-chronic knee pain; 43% of workers with incident chronic knee pain and 30% of workers with incident sub-chronic knee pain had other chronic pains at baseline, and respectively 51% and 28% reported limitations in climbing stairs. After adjustment for age and BMI, significant associations were found between incident knee pain and handling loads >4 kg (Odds-Ratio (OR) 2.1 (1.2–3.6) among men, OR 2.3 (1.1–5.0) among women) and kneeling for more than 2 h per day among men (OR 1.8 (1.0–3.0)). Conclusions: This study, conducted in a large representative working population, highlights the relation between incident knee pain and occupational risk factors such as handling loads and kneeling.